2014
DOI: 10.1039/c4ra06237j
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism for d0 ferromagnetism mediated by intrinsic defects

Abstract: We present insights into the role of vacancies and surface states in the d0 ferromagnetism of ZnS nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…31 In addition, FM originating from the vacancy related defects in the grain boundaries 32 and associated dangling bonds 33 in the present case cannot be completely excluded because spin-split can be due to the result of an exchange interaction between these intrinsic defects. 33 If the spin-splitting is larger than the band width, long range spin-polarization could be realized. 34 The formation of a defect band and its spin-splitting can be envisaged via electrical transport studies.…”
Section: Experiments Results and Discussionmentioning
confidence: 79%
“…31 In addition, FM originating from the vacancy related defects in the grain boundaries 32 and associated dangling bonds 33 in the present case cannot be completely excluded because spin-split can be due to the result of an exchange interaction between these intrinsic defects. 33 If the spin-splitting is larger than the band width, long range spin-polarization could be realized. 34 The formation of a defect band and its spin-splitting can be envisaged via electrical transport studies.…”
Section: Experiments Results and Discussionmentioning
confidence: 79%
“…Recently, we found that, in Zn-based semiconductors, the magnetic exchange took place between the electrons of two singly charged anion vacancies and that of a neutral anion vacancy, thus establishing FM coupling. 45 A similar mechanism can take place with Zn i or V O defect complexes. (iii) The third possible mechanism is Gd-mediated FM, whereby FM is induced by the defects and Gd stabilizes and mediates the exchange coupling between the defect state and host s electrons.…”
Section: (A)-4(c) Furthermore M Vs H/t Curves (Figs 4(d)-4(f)mentioning
confidence: 91%
“…While the ferromagnetism in ZnS is controversial, there is consensus that either Zn or S vacancies may be responsible for the ferromagnetic order. [36][37][38][39] When the Zn/S vacancies exceed a certain concentration, there may be sufficient overlap between their moments to induce ferromagnetic order. Due to its sensitivity limitation, our EDS measurements did not provide conclusive result as to which vacancies (Zn or S) were present in the samples.…”
Section: Resultsmentioning
confidence: 99%